PERAN BHABINKAMTIBMAS DALAM PENYELESAIAN KONFLIK SOSIAL DI WILAYAH HUKUM POLSEK MEJOBO KUDUS - Much. Kartika Novianto; Iskandar Wibawa (Cattleya Darmaya Fortuna, 2026)
Bhabinkamtibmas plays a strategic role as the spearhead of the Indonesian National Police (Polri) in maintaining public security and order through a non-litigation and restorative justice approach that prioritizes peaceful problem resolution . This study aims to analyze the role of Bhabinkamtibmas in resolving social conflicts within the jurisdiction of the Mejobo Kudus Police and the challenges faced in its implementation . This study uses a sociological juridical approach with descriptive analytical specifications to examine the relationship between legal norms and their implementation in the social dynamics of society . Data sources were obtained through primary data in the form of observations and in-depth interviews with Bhabinkamtibmas personnel and community leaders in the jurisdiction of the Mejobo Kudus Police . In addition, this study is supported by secondary data through library studies of various legal materials and related literature to strengthen the validity of the analysis. The results of the study show that the role of Bhabinkamtibmas in Settlement Conflict Social among others: Bhabinkamtibmas as a social mediator , Bhabinkamtibmas as detector early occurrence conflict social , Bhabinkamtibmas as facilitator deliberation, Bhabinkamtibmas as agent prevention conflict / preventive conflict , Bhabinkamtibmas as collaborator with figure community , Bhabinkamtibmas as educator / protector , Bhabinkamtibmas as implementer action curative . The main challenges faced by Bhabinkamtibmas in Settlement Conflict Social between other : limitations competence mediation and skills Special from Bhabinkamtibmas , weakness regulations and boundaries authority law , workload , ratio regional personnel , and resources Power limited , Complexity Sociocultural Local and Dynamic Leadership Local.